Performing Politics - Paddock, Troy R. E. (Contemporary Aesthetics, 2015)
Walter Benjamin’s observation that fascism turns politics into aesthetics is, by now, a well-worn idea. This article argues that Benjamin’s critique of politics can apply just as much to the modern democratic politics of the United States. Borrowing from Benjamin, Jürgen Habermas, and Carl Schmitt, this article suggests that modern political discourse in the United States does not follow the classical liberal ideal of rational discourse in the marketplace of ideas within the public sphere. Instead, contemporary politics has become spectacle where images and slogans replace thought and debate in a 24/7 news cycle and political infotainment programs. The result is that progressives and conservatives have their own political “ecospheres” which enable them to have their own perspective reinforced, and debate is replaced by straw man arguments and personal attacks.
Keywords: dept.his; ⛔ No DOI found